Transitioning from a single-site pilot project to a state-wide regional telehealth service: The experience from the Victorian Stroke Telemedicine programme. (December 2017) - Bagot, Kathleen L; Cadilhac, Dominique A; Kim, Joosup; Vu, Michelle; Savage, Mark; Bolitho, Les; Howlett, Glenn; Rabl, Justin; Dewey, Helen M; Hand, Peter J; Denisenko, Sonia; Donnan, Geoffrey A; et al.
Scaling of projects from inception to establishment within the healthcare system is rarely formally reported. The Victorian Stroke Telemedicine (VST) programme provided a very useful opportunity to describe how rural hospitals in Victoria were able to access a network of Melbourne-based neurologists via telemedicine. The VST programme was initially piloted at one site in 2010 and has gradually expanded as a state-wide regional service operating with 16 hospitals in 2017. The aim of this paper is to summarise the factors that facilitated the state-wide transition of the VST programme. A naturalistic case-study was used and data were obtained from programme documents, e.g. minutes of governance committees, including the steering committee, the management committee and six working groups; operational and evaluation documentation, interviews and research field-notes taken by project staff. Thematic analysis was undertaken, with results presented in narrative form to provide a summary of the lived experience of developing and scaling the VST programme. The main success factors were attaining funding from various sources, identifying a clinical need and evidence-based solution, engaging stakeholders and facilitating co-design, including embedding the programme within policy, iterative evaluation including performing financial sustainability modelling, and conducting dissemination activities of the interim results, including promotion of early successes.